Bio-based fiber-based antiviral home textile fabric and preparation method thereof
By modifying lignin fibers and nanobacterial cellulose and polylactic acid blended spinning technology, the organic metal frame structure is constructed, which solves the problem of insufficient durability and comfort of anti-viral home textile fabrics and achieves efficient anti-viral effects.
Patent Information
- Application Number
- CN202510704899.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2025-08-01
AI Technical Summary
Existing antiviral home textile fabrics have shortcomings in terms of durability and comfort, making it difficult to maintain efficient antiviral effects at the same time.
The modified lignin fiber is used to blend the spinning technology with nanobacterial cellulose and polylactic acid. The construction of ether bonds and organometallic frame structures is improved to improve the flexibility and antiviral activity of the fibers to prepare antiviral home textile fabrics.
Improves durability and comfort of anti-viral home textile fabrics while maintaining efficient anti-viral effects.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of home textile fabrics, and specifically to an antiviral home textile fabric based on bio-based fibers and a preparation method thereof. Background Art
[0002] With the increase of global public health events, people's attention to health, safety and environmental protection has been increasing day by day, which has promoted the application of antiviral and antibacterial fibers in various fields. Not only is the demand for antiviral fibers most significant in the medical field, but at the same time, industries such as home, clothing, and textiles have gradually become important markets.
[0003] The preparation technology of antiviral and antibacterial fibers has been continuously improved, including methods such as nanotechnology, biotechnology, and physical modification. The application of these technologies has significantly improved the performance of antiviral and antibacterial fibers. At the same time, characteristics such as environmental protection, non-toxicity, and degradability have also made antiviral and antibacterial fibers more favored by the market.
[0004] At present, bio-based fibers are prepared from renewable resources (such as corn starch, bagasse, cottonseed hulls, etc.) through bioconversion technologies (fermentation, polymerization, spinning, etc.), and have both degradability and natural antibacterial properties. For example, regarding antibacterial properties, the antibacterial rate of polylactic acid (PLA) fibers against Escherichia coli and Staphylococcus aureus can reach more than 90%.
[0005] In addition, in the field of textile fabrics, the realization of antiviral functions requires the combination of nanotechnology (such as silver ions, graphene) or natural extracts to inactivate the virus by destroying the virus membrane structure or inhibiting its metabolic activity. In this application, a home textile fabric is prepared through bio-based composite fibers. Regarding the durability of the fabric, the following solutions are proposed based on polylactic acid composite fibers. Summary of the Invention
[0006] This application provides an antiviral home textile fabric based on bio-based fibers and a preparation method thereof, which can maintain and improve the antiviral effect of the antiviral home textile fabric while increasing its durability.
[0007] An antiviral home textile fabric based on bio-based fibers provided by this application is characterized in that the spinning fibers of the home textile fabric are prepared by co-blending lactic acid fibers and functional fibers; the functional fibers include modified lignin fibers and nano bacterial cellulose. The raw materials of the modified lignin fibers include alkali lignin and polyethylene glycol; the nano bacterial cellulose is obtained by culturing a bacterial fiber membrane from a Acetobacter xylinum culture solution and then subjecting it to fragmentation and nanosizing; the nano bacterial cellulose is subjected to antiviral functionalization treatment, including the construction of an organic metal framework structure.
[0008] By adopting the above technical solution, the raw materials of the modified lignin fiber in the present application include alkali lignin and polyethylene glycol. Polyethylene glycol undergoes a grafting reaction with lignin hydroxyl groups through ether bonds to form a stable chemical bonding structure. The introduction of polyethylene glycol reduces the rigidity of alkali lignin and improves its compatibility with matrices such as polylactic acid (PLA), thereby increasing the elongation at break and enhancing the flexibility and comfort of the composite fiber. In addition, the functionalized fiber in the present application also includes nano-bacterial cellulose. The present application obtains a bacterial fiber membrane by culturing Acetobacter xylinum culture solution, which is obtained through fragmentation and nano-sizing, and the nano-bacterial cellulose is subjected to antiviral functionalization treatment; nano-bacterial cellulose can not only be directly processed by wet spinning without strong acid or strong base treatment, and the production waste can be biodegradable, but also the nano-bacterial cellulose prepared based on biological fibers has an extremely high specific surface area and strong tensile strength, and through the construction of an organic metal framework (MOF) structure, it provides antiviral activity, enabling the antiviral home textile fabric in the present application to not only have the effect of antiviral, but also improve the comfort and durability of the antiviral home textile fabric during use.
[0009] On the other hand, the present application provides a preparation method of an antiviral home textile fabric based on bio-based fibers, including the following operation steps: preparation of modified lignin fiber, nano-sizing and preparation of bacterial cellulose, spinning and finishing of composite fiber, and fabric weaving and post-finishing.
[0010] Preferably, the preparation of the modified lignin fiber includes the following operation steps: placing alkali lignin and polyethylene glycol in a vacuum melting reaction kettle in a certain proportion, mixing, controlling a certain vacuum degree, heating to a certain temperature and stirring evenly for a certain time, and naturally cooling after the reaction ends to obtain the modified lignin fiber.
[0011] Preferably, the nano-sizing and preparation of the bacterial cellulose includes the following operation steps: S1. Fermentation to prepare a bacterial fiber membrane: statically culturing the Acetobacter xylinum culture solution at a certain temperature for a certain time to form a gel-like bacterial fiber membrane, then rinsing with deionized water, treating with a NaOH solution of a certain concentration for a certain time, then removing the bacterial residue, and then bleaching with sodium hypochlorite to obtain the bacterial fiber membrane; S2. Fiber nano-sizing treatment: crushing the bacterial fiber membrane and then treating it with a high-pressure homogenizer to obtain nano-bacterial cellulose, and then immersing the nano-bacterial cellulose in an ethanol solution of a silane coupling agent to obtain pretreated nano-bacterial cellulose; S3. Antiviral functionalization treatment: impregnating the pretreated nano-bacterial cellulose in an L-cysteine solution at a certain concentration, oscillating at a certain temperature for a certain time, then dropping a CuSO4 solution of a certain concentration, reacting at a certain temperature, and then adding a 2-methylimidazole solution of a certain concentration, and standing at room temperature to generate nano-sized bacterial cellulose particles.
[0012] Preferably, the spinning finishing of the composite fiber includes the following operating steps: putting modified lignin, nano-sized bacterial cellulose particles, and polylactic acid chips into a twin-screw extruder in a certain proportion, mixing them at a certain temperature to obtain a composite fiber masterbatch, and then preparing the composite fiber from the composite fiber masterbatch through a melt spinning machine.
[0013] Preferably, the fabric weaving and post-finishing include the following operating steps: doubling and twisting the composite fiber, controlling the spindle speed of the flyer at 9000 - 15,000 revolutions per minute, and the twist at 50 - 90 twists / 10 cm to obtain a composite fiber yarn, then using a rapier loom with a warp and weft density of 50 threads / cm to prepare a fabric greige. Soak the fabric greige in water at 70 - 80 °C for 0.5 - 2 hours to remove the sizing and impurities; then bleach it with sodium hypochlorite to pure white. Finally, add an anionic dye to the fabric greige in a dyeing vat and fix the color with an alkaline agent, with a dyeing temperature of 50 - 80 °C and a time of 0.5 - 1.5 h to obtain a home textile fabric.
[0014] Preferably, in the preparation step of the modified lignin fiber, the weight ratio of the alkali lignin to the polyethylene glycol is 1 - 3:2 - 6.
[0015] By adopting the above technical solution, in this application, polyethylene glycol is used to react with the lignin hydroxyl group through an ether bond, reducing the rigidity of lignin and enhancing its compatibility with polylactic acid, improving the elongation at break, and endowing the home textile fabric with flexibility and comfort.
[0016] Preferably, in the antiviral functionalization treatment step, 10 - 20 mL of L-cysteine solution with a mass fraction concentration of 5% is required for each gram of pretreated nano-bacterial cellulose; 1 - 2 mL of CuSO4 solution with a concentration of 0.1 mol / L is required for each gram of pretreated nano-bacterial cellulose; the molar ratio of the 2-methylimidazole solution to the CuSO4 solution is 2:1, and the concentration of the 2-methylimidazole solution is 0.1 mol / L.
[0017] By adopting the above technical solution, in the application, during the antiviral functionalization treatment of nano-bacterial cellulose, first, the mercapto (-SH) of L-cysteine forms a thioester bond with the hydroxyl group on the surface of nano-bacterial cellulose, providing an anchoring site for subsequent metal ion loading; secondly, copper ions (Cu 2+ ) coordinate with the thioester bond of L-cysteine to form a stable metal-sulfur coordination structure, providing metal nodes for the growth of metal-organic frameworks (MOFs); finally, 2-methylimidazole, as an organic ligand, self-assembles with Cu 2+ through coordination bonds to form a ZIF-8 type metal-organic framework (MOF) structure, which helps to improve the adsorption and inactivation performance of the antiviral fabric.
[0018] Preferably, in the spinning and finishing step of the composite fiber, the weight ratio of modified lignin, nano-sized bacterial cellulose particles, and polylactic acid chips is 15-25: 2-10: 65-83.
[0019] Preferably, in the spinning and finishing step of the composite fiber, modified lignin, nano-sized bacterial cellulose particles, and polylactic acid chips are at 150-180 °C, with a screw speed of 60-100 rpm, to obtain a composite fiber masterbatch. Through a melt spinning machine spinneret with a pore diameter of 0.1-0.3 mm and a temperature of 170-220 °C, and a winding speed of 800-1200 m / min, the composite fiber is prepared.
[0020] By adopting the above technical solution, in the spinning and finishing step of the composite fiber of the present application, the blending granulation parameters and melt spinning parameters need to be controlled. Among them, first, the thermal decomposition temperature of alkali lignin modified by polyethylene glycol is significantly increased. Polyethylene glycol undergoes a grafting reaction with the hydroxyl group of alkali lignin through an ether bond to form a stable chemical bonding structure. This covalent bond remains stable under the high temperature of 150-180 °C and high shear force environment of a twin-screw extruder, as well as during melt spinning at 228 °C, avoiding the breakage or degradation of lignin molecular chains and the destruction of the microstructure caused by interfacial tension.
[0021] In addition, the metal-organic framework (MOF) and nano-bacterial cellulose form a chemical bond through the thioester bond (-S-S-) of L-cysteine and the coordination bond of copper ions. This strong interfacial interaction can resist the destruction of the high shear force (shear rate of about 100-500 s -1 ) and melting temperature (160-180 °C) of the twin-screw extruder, and the metal-organic framework (MOF) grows directly on the surface of nano-bacterial cellulose through in-situ hydrothermal synthesis (rather than physical mixing), avoiding physical breakage caused by friction during the extrusion process. In addition, during the extrusion process, the graft formed between polyethylene glycol and alkali lignin in the present application reduces the aggregation of metal-organic framework (MOF) particles through hydrogen bonds and van der Waals forces, while reducing the mechanical damage of the screw shear force to the surface of the metal-organic framework (MOF).
[0022] In the process of the present application, by adjusting the proportion of the addition amounts of modified lignin, nano-sized bacterial cellulose particles, and polylactic acid chips, and simultaneously adjusting the parameters of blending granulation and melt spinning, the spinning of the composite fiber can be carried out without destroying the structures of the three components, thereby improving the comfort and durability of the antiviral home textile fabric during use.
[0023] One or more technical solutions provided in the present application have at least the following technical effects or advantages:
[0024] 1. In this application, the raw materials of the modified lignin fiber include alkali lignin and polyethylene glycol. Polyethylene glycol undergoes a grafting reaction with lignin hydroxyl groups through ether bonds to form a stable chemical bonding structure. The introduction of polyethylene glycol reduces the rigidity of alkali lignin and improves its compatibility with matrices such as polylactic acid (PLA), thereby increasing the elongation at break and enhancing the flexibility and comfort of the composite fiber.
[0025] 2. In this application, a bacterial fiber membrane is obtained by culturing with Acetobacter xylinum culture solution, and is obtained after being broken and nano-sized. The nano-bacterial cellulose is subjected to antiviral functionalization treatment; and the nano-bacterial cellulose prepared based on bio-fiber has an extremely high specific surface area and extremely strong tensile strength, and through the construction of an organic metal framework (MOF) structure, antiviral activity is provided.
[0026] 3. In this application, by adjusting the proportion of the addition amounts of modified lignin, nano-sized bacterial cellulose particles, and polylactic acid chips, and simultaneously adjusting the parameters of melt blending granulation and melt spinning, the spinning of composite fibers can be carried out without destroying the structures of the three, thereby improving the durability of the antiviral home textile fabric during use. Detailed implementation manners
[0027] This application provides an antiviral home textile fabric based on bio-based fibers and its preparation method, which can maintain and improve the antiviral effect of the antiviral home textile fabric while increasing its durability.
[0028] Next, in combination with the embodiments of this application, the technical solutions in the embodiments of this application will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of this application, rather than all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the scope protected by this application.
[0029] It should be noted that the terms "first", "second", etc. in the description and claims of this application are used to distinguish similar objects, and do not necessarily need to be used to describe a specific order or sequence. It should be understood that such data can be interchanged under appropriate circumstances so that the embodiments of this application described here can be implemented in an order other than those described here. In addition, the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product, or server that includes a series of steps or units does not necessarily have to be limited to those steps or units clearly listed, but may include other steps or modules that are not clearly listed or are inherent to these processes, methods, products, or devices.
[0030] Embodiments
[0031] Example 1
[0032] 1. Preparation of modified lignin fiber:
[0033] Mix alkali lignin (purity ≥ 95%) and polyethylene glycol (PEG2000) in a weight ratio of 1:3 in a vacuum melting reactor, heat up to 160 °C, maintain the vacuum degree ≤ 0.1 MPa, and stir evenly with a double spiral ribbon stirrer (rotation speed 80 rpm) for 3 hours. After the reaction is completed, cool naturally to room temperature to obtain modified lignin fiber.
[0034] 2. Nanometerization and preparation of bacterial cellulose:
[0035] S1. Fermentation to prepare bacterial fiber membrane: Static culture the Acetobacter xylinum culture solution (pH = 4.8, containing 23 g / L glucose, 6 g / L yeast extract, 3 g / L dipotassium hydrogen phosphate) at 30 °C for 5 days to form a gel-like bacterial fiber membrane with a thickness of 1 - 2 mm. Then rinse it three times with deionized water, treat it with 0.1 M NaOH solution for 2 hours, then remove the residual bacteria, and bleach it with sodium hypochlorite to obtain the bacterial fiber membrane;
[0036] S2. Fiber nanometerization treatment: After crushing the bacterial fiber membrane, treat it with a high-pressure homogenizer (120 MPa, 3 cycles) to obtain nanometer bacterial cellulose. Then immerse the nanometer bacterial cellulose in an ethanol solution of 5 wt% 3-aminopropyltriethoxysilane (APTES) for 2 hours at a temperature of 60 °C to form a coordination bond between the amino group and the subsequent Cu2O, obtaining pretreated nanometer bacterial cellulose;
[0037] S3. Antiviral functionalization treatment: Immerse 100 g of pretreated nanometer bacterial cellulose in 1 L of 5% L-cysteine solution, oscillate at 60 °C for 1 hour to form a thioester bond, then dropwise add 100 ml of 0.1 mol / L CuSO4 solution and react at 60 °C for 2 hours. The copper ions coordinate with the thioester bond. Finally, add 200 ml of 0.1 mol / L 2-methylimidazole solution and let it stand at room temperature for 12 hours to generate nanometerized bacterial cellulose particles.
[0038] 3. Spinning finishing of composite fiber:
[0039] Put modified lignin, nanometerized bacterial cellulose particles, and polylactic acid chips in a weight ratio of 15:2:83 into a twin-screw extruder. At 150 °C, with a screw rotation speed of 60 rpm, obtain a composite fiber masterbatch. Through a melt spinning machine with a spinneret hole diameter of 0.2 mm, a temperature of 170 °C, and a winding speed of 1000 m / min, prepare the composite fiber.
[0040] 4. Fabric weaving and post-finishing:
[0041] The composite fibers are combined and twisted, with the spindle speed controlled at 12,000 revolutions per minute and the twist of 80 turns per 10 cm to obtain composite fiber yarns. Then, a rapier loom is used with a warp and weft density of 50 threads per cm to prepare a fabric greige. The fabric greige is soaked in water at 80 °C for 1.5 hours to remove the sizing agent and impurities, then bleached with sodium hypochlorite to pure white. Finally, anionic dyes are added to the fabric greige in a dyeing vat and fixed with an alkali agent at a dyeing temperature of 60 °C for 1 hour to obtain an antiviral home textile fabric.
[0042] Examples 2 - 4
[0043] The differences between Examples 2 - 4 and Example 1 lie in that in the preparation steps of the modified lignin fibers, the weight ratio of alkali lignin to polyethylene glycol is different.
[0044] Examples 5 - 7
[0045] The differences between Examples 5 - 7 and Example 1 lie in that in the antiviral functionalization treatment steps, the addition of L-cysteine solution, CuSO4 solution, and 2-methylimidazole solution is different.
[0046] Examples 8 - 9
[0047] The differences between Examples 8 - 9 and Example 1 lie in that in the spinning and finishing steps of the composite fibers, the parameters regarding the co-blending and pelletizing parameters are different, including the weight fraction ratios of modified lignin, nano-sized bacterial cellulose particles, and polylactic acid chips.
[0048] The above parameters are organized into the following table
[0049] Table 1. Parameter table for the preparation of composite fibers in Examples 1 - 9
[0050]
[0051] Examples 10 - 12
[0052] The differences between Examples 10 - 12 and Example 1 lie in that in the spinning and finishing steps of the composite fibers, the parameters of co-blending pelletizing and melt spinning are different; and the parameters are organized into the following table.
[0053] Table 2. Parameter table for co-blending pelletizing and melt spinning in Example 1 and Examples 10 - 12
[0054]
[0055] Comparative Example
[0056] Comparative Example 1
[0057] The difference between Comparative Example 1 and Example 1 is that in the spinning and finishing step of the composite fiber, modified lignin was not added; the main components of the composite fiber for preparing the antiviral home textile fabric are bacterial cellulose and polylactic acid.
[0058] Comparative Example 2
[0059] The difference between Comparative Example 2 and Example 1 is that in the spinning and finishing step of the composite fiber, nano-sized bacterial cellulose particles were not added; the main components of the composite fiber for preparing the antiviral home textile fabric are modified lignin and polylactic acid.
[0060] Comparative Example 3
[0061] The difference between Comparative Example 3 and Example 1 is that the lignin fiber was not modified with polyethylene glycol.
[0062] Comparative Example 4
[0063] The difference between Comparative Example 4 and Example 1 is that the nano-bacterial cellulose was not subjected to antiviral functionalization treatment.
[0064] Performance detection experiment
[0065] The antiviral home textile fabrics prepared in Examples 1 - 12 and Comparative Examples 1 - 4 were tested.
[0066] 1. Antiviral performance detection
[0067] In this application, according to Standard ISO 18184:2019, the virus suspension was directly dropped or sprayed on the surface of the textile to simulate the actual contact scenario, and the antiviral effect was evaluated by detecting the virus residue. A quantitative virus suspension was dropped on the specimen and incubated at 25 °C for 2 hours; the virus was eluted by vortex oscillation using an eluent (such as SCDLP liquid medium), and the eluate was collected for dilution; the surviving virus was quantified by the TCID50 method (median tissue culture infective dose method); and the antiviral activity value (Mv) was calculated.
[0068] 2. Tensile strength detection
[0069] In this application, according to GB / T 3923.1 - 2013, the determination of the breaking strength and elongation at break of the fabric was detected (strip method). The width of the specimen was 50 mm ± 0.5 mm, the gauge length was usually 200 mm, the tensile speed was 100 mm / min, the specimen was stretched to break at a constant speed by a tensile testing machine, and the elongation at break was recorded.
[0070] 3. Bursting strength detection
[0071] This application uses GB / T 19976-2005 (steel ball method). The specimen is vertically pierced by a steel ball ejector. The diameter of the specimen is ≥45 mm, the diameter of the steel ball is 25 mm or 38 mm (38 mm is commonly used), the loading speed is 300 mm / min, and the maximum force value is recorded.
[0072] Table 3. Detection data table of Examples 1-12 and Comparative Examples 1-4
[0073]
[0074] Data analysis
[0075] This application analyzes between Example 1 and Comparative Example 1. The difference between Comparative Example 1 and Example 1 is that in the spinning and finishing step of the composite fiber, modified lignin is not added; the main components of the composite fiber for preparing the antiviral home textile fabric are bacterial cellulose and polylactic acid. Therefore, in the detection and analysis process, the data of the breaking strength test and bursting strength test of the antiviral home textile fabric in Comparative Example 1 are weaker than those in Example 1.
[0076] In addition, in combination with Comparative Example 3, the difference between Comparative Example 3 and Example 1 is that the lignin fiber is not modified by polyethylene glycol. Among them, the data of the breaking strength test and bursting strength test of the antiviral home textile fabric in Comparative Example 3 are weaker than those in Example 1. This is because polyethylene glycol undergoes a grafting reaction with lignin hydroxyl groups through ether bonds to form a stable chemical bonding structure. The introduction of polyethylene glycol reduces the rigidity of alkali lignin and improves its compatibility with matrices such as polylactic acid (PLA), thereby increasing the elongation at break. Therefore, the modification by adding polyethylene glycol can greatly increase the mechanical properties of the home textile fabric.
[0077] In addition, the difference between Comparative Example 2 and Example 1 is that in the spinning and finishing step of the composite fiber, nano-sized bacterial cellulose particles are not added; the main components of the composite fiber for preparing the antiviral home textile fabric are modified lignin and polylactic acid. According to the data analysis in Table 3, nano-bacterial cellulose with antiviral functionalization can greatly improve the antiviral effect of the home textile fabric.
[0078] And in combination with Comparative Example 4, the difference between Comparative Example 4 and Example 1 is that nano-bacterial cellulose is added in the spinning and finishing step of the composite fiber, but the nano-bacterial cellulose is not subjected to antiviral functionalization. Among them, nano-bacterial cellulose prepared based on biological fibers has an extremely high specific surface area and extremely strong tensile strength, and through the construction of an organic metal framework (MOF) structure, it provides antiviral activity.
[0079] For the analysis of Examples 1-4, in the preparation steps of the modified lignin fiber, the weight ratio of alkali lignin to polyethylene glycol is different; for the analysis of Examples 5-7, in the antiviral functionalization treatment steps, the addition of nanocellulose bacteria, L-cysteine solution, CuSO4 solution, and 2-methylimidazole solution is different; and for Examples 8-9, in the spinning finishing steps of the composite fiber, the parameters regarding the blending granulation parameters are different, including the weight fraction ratio of modified lignin, nanosized bacterial cellulose particles, and polylactic acid chips; the above factors will all lead to different antiviral effects and durability of the home textile fabrics. In summary, Example 1 is the optimal example.
[0080] In addition, during the construction of the metal-organic framework (MOF) in this application, the addition amount of the CuSO4 solution determines the content of cuprous oxide in the fabric. Currently, according to the toxicity risk of cuprous oxide, if the particle size is too small (such as <60 nm), extracellular toxicity may occur, and the particle diameter needs to be controlled >60 nm; and the content of cuprous oxide generally should not exceed 15%. Unless in high-functional demand scenarios (such as medical protective materials), through stretching technology or multi-stage dispersion process, the addition amount of Cu2O can be increased to 15% - 20%. In Examples 5-7 of this application, the addition amount of the CuSO4 solution is maintained within the safe range of the textile fabric. At the same time, regarding the metal-organic framework (MOF) synthesized by CuSO4 and 2-methylimidazole, the diameter of the cuprous oxide particles generated after pyrolysis or reduction is usually 100 - 120 nm, thus eliminating potential safety hazards.
[0081] Finally, regarding the analysis of Examples 10-12, in the spinning finishing steps of the composite fiber in Examples 10-12, the parameters of blending granulation and melt spinning are different. Specifically, Example 11 is the optimal example.
[0082] In this application, the parameters of blending granulation and melt spinning are obtained through multiple experiments. Among them, polyethylene glycol undergoes a grafting reaction with the hydroxyl group of alkali lignin through an ether bond to form a stable chemical bonding structure. This covalent bond remains stable under the high temperature of 150 - 180 °C and high shear force environment of the twin-screw extruder, as well as during melt spinning at 228 °C, avoiding the breakage or degradation of the lignin molecular chain and the destruction of the microstructure caused by interfacial tension. Therefore, it is ensured that the temperature during melt spinning cannot exceed 228 °C, with 200 °C being the best. At the same time, the optimal melt spinning temperature of polylactic acid is 170 - 230 °C, so it is within the melt spinning range of polylactic acid. In addition, the metal-organic framework (MOF) and nanocellulose bacteria form a chemical bond through the thioester bond (-S-S-) of L-cysteine and the coordination bond of copper ions, and can also resist the high shear force of the twin-screw extruder (shear rate of about 100 - 500 s -1) and the destruction of the melting temperature (160 - 180 °C), and the metal-organic framework (MOF) is directly grown on the surface of nanocellulose bacteria by in-situ hydrothermal synthesis (rather than physical mixing), avoiding physical breakage caused by friction during the extrusion process.
[0083] It should be noted that the above order of the embodiments of the present application is only for description and does not represent the superiority or inferiority of the embodiments. And the above specific embodiments of the present specification have been described. Other embodiments are within the scope of the appended claims. In some cases, the actions or steps recited in the claims can be executed in a different order than in the embodiments and still achieve the desired results. In certain embodiments, multitasking and parallel processing are also possible or may be advantageous.
[0084] The above are only the preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
[0085] This specification is only an exemplary illustration of the present application and is considered to cover any and all modifications, variations, combinations, or equivalents within the scope of the present application. Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the present application and its equivalent technologies, the present application is intended to include these changes and modifications.
Claims
1. An antiviral home textile fabric based on bio-based fibers, characterized in that, The spinning fibers of the home textile fabric are prepared by blending lactic acid fibers and functional fibers; The functional fibers include modified lignin fibers and nano bacterial cellulose; The raw materials of the modified lignin fibers include alkali lignin and polyethylene glycol; The nano bacterial cellulose is obtained by culturing a bacterial fiber membrane from a Acetobacter xylinum culture solution and then subjecting it to nano-scale fragmentation; The nano bacterial cellulose is subjected to antiviral functionalization treatment, including the construction of an organic metal framework structure.
2. A preparation method of an antiviral home textile fabric based on bio-based fibers as described in claim 1, characterized in that, It includes the following operating steps: preparation of modified lignin fibers, nano-scale fragmentation and preparation of bacterial cellulose, spinning finishing of composite fibers, and fabric weaving and post-finishing.
3. The preparation method of an antiviral home textile fabric based on bio-based fibers according to claim 2, characterized in that The preparation of the modified lignin fibers includes the following operating steps: placing alkali lignin and polyethylene glycol in a vacuum melting reaction kettle in proportion, controlling the vacuum degree, heating up and stirring evenly, and naturally cooling after the reaction ends to obtain modified lignin fibers.
4. The preparation method of an antiviral home textile fabric based on bio-based fibers according to claim 3, characterized in that, The nano-scale fragmentation and preparation of the bacterial cellulose includes the following operating steps: S1. Fermentation to prepare a bacterial fiber membrane: statically culturing the Acetobacter xylinum culture solution to form a gel-like bacterial fiber membrane, then rinsing with deionized water, treating with a NaOH solution for a certain time, then removing the bacterial residue, and then bleaching with sodium hypochlorite to obtain a bacterial fiber membrane; S2. Fiber nano-scale fragmentation treatment: crushing the bacterial fiber membrane and then treating it with a high-pressure homogenizer to obtain nano bacterial cellulose, and then immersing the nano bacterial cellulose in an ethanol solution of a silane coupling agent to obtain pretreated nano bacterial cellulose; S3. Antiviral functionalization treatment: immersing the pretreated nano bacterial cellulose in an L-cysteine solution, oscillating for a certain time, then dropping CuSO4 solution, and then adding 2-methylimidazole solution, and standing at room temperature to generate nano-scale bacterial cellulose particles.
5. The preparation method of an antiviral home textile fabric based on bio-based fibers according to claim 4, characterized in that, The spinning finishing of the composite fibers includes the following operating steps: Putting modified lignin, nano-scale bacterial cellulose particles, and polylactic acid chips into a twin-screw extruder in a certain proportion, mixing at a certain temperature to obtain a composite fiber masterbatch, and then preparing composite fibers from the composite fiber masterbatch through a melt spinning machine.
6. The preparation method of an antiviral home textile fabric based on bio-based fibers according to claim 4, characterized in that, The fabric weaving and post-finishing includes the following operating steps: Twisting and combining the composite fibers, controlling the spindle speed at 9000 - 15,000 revolutions per minute and the twist at 50 - 90 twists per 10 cm to obtain composite fiber yarns, and then using a rapier loom with a warp and weft density of 50 threads / cm to prepare a fabric greige. Soaking the fabric greige in water at 70 - 80 °C for 0.5 - 2 hours to remove sizing agents and impurities; then bleaching with sodium hypochlorite to pure white, and finally adding an anionic dye to the fabric greige in a dyeing vat and fixing the color with an alkali agent at a dyeing temperature of 50 - 80 °C for 0.5 - 1.5 h to obtain the home textile fabric.
7. The preparation method of an antiviral home textile fabric based on bio-based fibers according to claim 3, characterized in that, In the preparation step of the modified lignin fibers, the weight ratio of the alkali lignin to the polyethylene glycol is 1 - 3:2 - 6.
8. The preparation method of an antiviral home textile fabric based on bio-based fibers according to claim 4, characterized in that, In the antiviral functionalization treatment step, 10 - 20 mL of L-cysteine solution is required for each gram of pretreated nano bacterial cellulose, and the mass fraction of the concentration of the L-cysteine solution is 5%; 1 - 2 mL of CuSO4 solution with a concentration of 0.1 mol / L is required for each gram of pretreated nanocellulose bacteria; The molar ratio of the 2 - methylimidazole solution to the CuSO4 solution is 2:1, and the concentration of the 2 - methylimidazole solution is 0.1 mol / L.
9. The preparation method of an antiviral home textile fabric based on bio-based fibers according to claim 5, characterized in that, In the spinning and finishing step of the composite fiber, the weight ratio of modified lignin, nanosized bacterial cellulose particles, and polylactic acid chips is 15 - 25:2 - 10:65 - 83.
10. The preparation method of an antiviral home textile fabric based on bio-based fibers according to claim 9, characterized in that, In the spinning and finishing step of the composite fiber, modified lignin, nanosized bacterial cellulose particles, and polylactic acid chips are at 150 - 180 °C, with a screw speed of 60 - 100 rpm to obtain a composite fiber masterbatch. Through a melt spinning machine with a spinneret hole diameter of 0.1 - 0.3 mm, a temperature of 170 - 220 °C, and a winding speed of 800 - 1200 m / min, the composite fiber is prepared.
Citation Information
Cited By
A method for preparing a modified bacterial cellulose
CN122628375A